MEDIATION OF STUDENT INTRINSIC MOTIVATION BETWEEN ONLINE LEARNING ENVIRONMENT AND STUDENT ENGAGEMENT - Magtubo, Rc Yhobel V.; Banal, Jerica Joyce; Abregado, Vincent Alex D.; Chavez, Ronald Allan Carlo S.; Embalsado, Justin Vianey Mercado (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2022)
The shift to a full online learning environment (OLE) introduces new challenges which affect the motivation and engagement of students. This study investigates the relationship between the online learning environment and online student engagement as mediated by intrinsic motivation. The self-system model of motivational development (SSMMD) was used as the framework of the study. The researchers hypothesized that intrinsic motivation will partially mediate the relationship between the online learning environment (OLE) and online student engagement (OSE). 255 college students completed the survey. GLM mediation analysis was conducted using JAMOVI. Our analysis shows that the online learning environment significantly predicts online student engagement (β = 0.553, p001). A decrease in regression weight with the direct effect was observed with the inclusion of intrinsic motivation as a mediator (β = .430, p.001). Even with the inclusion of intrinsic motivation, the direct effect of OLE on OSE remained significant. The indirect effect was also significant using the Corrected bias bootstrap percentile with 1000 repetitions (β = 0.127, p = 0.002, 95% CI [0.0245, 0.103]). Findings support the hypothesized partial mediation of intrinsic motivation between OLE and OSE.